STRATEGI PENINGKATAN MUTU PELAYANAN PADA TOKO HERBA PENAWAR AL-WAHIDA INDONESIA (HPAI) CABANG SIAK DITINJAU DARI ETIKA BISNIS ISLAM - Wiwik Indra Mariana; Raudhatul Jannah (Al-Hasyimiyah: Jurnal Ekonomi Syariah, 2025)
This study aims to analyze strategies for improving service quality at the Herba Penawar Al-Wahida Indonesia (HPAI) Siak Branch reviewed from the perspective of Islamic Business Ethies. This research uses a qualitative approach with a field study method. Data collection techniques include observation, interviews and documentation with data analysis techniques including data reduction, data presentation, drawing conclusions. Researchers use the TQS (Total Quality Service) theory which is part of TQM (Total Quality Management). The researcher‟s data analysis technique uses the data that has been obtained, then the data is analyzed using inductive thinking. The result of the study are that the head of the Siak HPAI Branch must provide a positive response, training and thoroughness to ensure the loyalty of the service provided by employees to consumers, for example First, Intangibility: training employees to be smart in ensuring and convincing potential consumers to be interested in achieving their desire to have HPAI products, such as employees are required to be friendly, responsive and reactive, have a neat appearance and openness about the product. Second, Heterogeneity: the act of providing SOP/ Matrix education to all HPAI employees, receiving input, providing effective communication training, and conducting continuous evaluations. Third, Inseperability: train employees not to delay providing solition to cunsumers who need advice, calm angry customers and be careful in communicating by paying attention to speaking style so they can respond positively to consumer intentions. Fourth, Perishability: consumer trust. market